ORGANIZATIONAL CULTURE AND CLIMATE AS THE REQUIREMENTS OF INNOVATION IN ORGANIZATIONS - Stevanovic, dr Ana (International Journal of Economic Practice and Policy, 2018)
Organizational innovation is a popular field of study in various disciplines including business, economics, engineering, psychology, public administration and sociology because it is seen as a key concept of economic growth and new industries. It creates competitive advantage and impact of the company, contributing to organizational effectiveness and competitiveness.Organizational innovation is often defined by two similar and related concepts: creativity and change. Even though the literature on innovation is fruitful, there has been a lack of connection with its predecessor - the organizational creativity, as well as an apparent lack of scientific studiesconducted in  organizational context. In order to introduce organizational innovations, as a result of organizational changes, the duty of a leader is to persuade employees to accept risk, to motivate them. Furthemore, they have to to gain their trust which is consistent with transformational leadership – a kind of leadership that aims to create a climate for innovation and has been recognized in literature as an important factor. Therefore, organizational culture and climate are preconditions for innovation within organizations in the same manner as risk-taking, experimentation, openness, trust and autonomy are part of the organizational support which provides the basis for innovation. That is the reason why organizational culture and climate promote creativity and innovation in companies and organizations.